Epilepsy-associated tumours: what epileptologists should know about neuropathology, terminology, and classification systems - Holthausen, Hans; Blümcke, Ingmar (Epileptic Disorders, 2016)
Brain tumours are an ever-challenging issue in neurology and related medical disciplines. This applies in particular to brain tumours associated with childhood-onset epilepsies, in which seizures are the presenting and only neurological symptom, as our current understanding of the biology and clinical behaviour of an individual tumour is far from being evidence-based. Prospective and randomized clinical trials are lacking in the field of epilepsy-associated tumours and a review of the current literature evokes more questions than provides answers. In this review, current areas of controversy in neuropathology, as well as terminology and classification, are discussed from an epileptologist's perspective. An illustrative case report exemplifies this controversy to further promote interdisciplinary discussion and novel research avenues towards comprehensive patient management in the near future.
EVALuna2:7343